FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI NELAYAN DALAM PROGRAM ASURANSI NELAYAN DI KABUPATEN PESISIR SELATAN - Farid Al Rasyid; Fitri Eriyanti (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research about rejected of fisherman’s participation in the insurance program in the Kabupaten Pesisir Selatan. The research objective of this research is to study and analyze social capital the participation of fishermen’s insurance program in Pesisir Selatan Regency. The Research wan conducted on fishermen who participated in the fishermen’s insurance program using propotional random sampling method of responden selection, The total population wa 272 fishermen and the sampling in this study is 54 people. To analiyzed social capital in participation in fishermen participation, it uses the Likert scale and the result of the study are partially social do not have participation in participation of fishermen in the fishermen’s insurance program in the Pesisir Selatan Regency.